PROJETO RECICLA TRÊS RIOS UM CASO DE SUCESSO EM EDUCAÇÃO AMBIENTAL E EMPREENDEDORISMO - Diniz Neto, Américo (2005)
This research evaluates the Recicla Três Rios Project, concerning its actions for environmental education, entrepreneurship and sustainability that results in changes of attitude among the community of Três Rios, in the state of Rio de Janeiro. This experiense is know, in many cities in state, as gathering selective program, where the society was involved, into a search for better quality of life. The awareness the importance of treating solid residues, converting them into employement and income many times obtained by informal activities, promoting the social inclusion in the city.